Number 43 (February 2002) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2002)
(February 2002) - Louisiana's inland fisheries: a quarter century of change. By Neil H. Douglas and Robyn J. Jordan Minutes, Business Meeting, 27th Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports Book Review: Dangerous Wildlife in the Southeast: A Guide to Safe Encounters at Home and in the Wild, by Lynn F. Bachleda, as reviewed by Martin O'Connell
Keywords: louisiana; fisheries; fishes